Judicial Flexibility in Imposing Sentences Below The Special Minimum Following The Recodification of The National Criminal Code: An Analysis of Sentencing Guidelines and Judicial Discretion - Rahmahwati Silvia Riani; Titin Nurfatlah (Universitas Katolik Indonesia Atma Jaya, 2026)
The enactment of Law Number 1 of 2023 on the Criminal Code (Kitab Undang-Undang Hukum Pidana/KUHP) represents a significant development in the reform of Indonesian criminal law and the evolution of the national legal system. The new Criminal Code reinforces the principle of legality, which provides that no person may be held criminally liable or punished for an act unless such act has been clearly regulated by legislation. This study employs normative legal research using a statutory approach. The data used consist of secondary legal materials, including primary legal materials in the form of relevant legislation and secondary legal materials comprising previous studies and judicial decisions in which judges imposed sentences below the special statutory minimum in corruption cases.This study examines judicial flexibility in imposing sentences below the special minimum following the recodification of the National Criminal Code. The sentencing guidelines stipulated in Article 54 paragraphs (1) and (2) of the Criminal Code should be understood as guidelines oriented toward a rehabilitative and restorative approach, with the aim of facilitating the improvement of offenders following the commission of a criminal offense. Nevertheless, these provisions should not be interpreted as granting judges unrestricted authority to impose sentences below a statutory special minimum. Rather, the sentencing guidelines serve as a framework for judges in adjudicating criminal cases in order to minimize excessive sentencing disparities while taking into account not only the defendant's degree of culpability but also humanitarian considerations, including the defendant's motives, objectives, state of mind, the consequences of the offense, and the response of society. Judicial flexibility following the recodification of the National Criminal Code remains necessary to realize substantive justice in sentencing. Nevertheless, such flexibility must be exercised in a measurable and reasoned manner and remain within the framework of the principle of legality. Judicial flexibility should therefore not be understood as unrestricted authority, but rather as the legally recognized scope within which judges may determine the type and severity of punishment that is most proportionate to the circumstances of the case and the sentencing guidelines set forth in Article 54 of the Criminal Code.